CD24 and PRAME Are Novel Grading and Prognostic Indicators for Pineal Parenchymal Tumors of Intermediate Differentiation. (January 2020) - Wu, Xuehui; Wang, Wei; Lai, Xiangmeng; Zhou, Yangshu; Zhou, Xue; Li, Jiaoying; Liang, Yunshi; Zhu, Xiaohui; Ren, Xiaoli; Ding, Yanqing; Liang, Li
Abstract : The pineal parenchymal tumors of intermediate differentiation (PPTIDs) are extremely rare tumor entities. They exhibit low-risk (grade II) and high-risk (grade III) malignancies, which may lead to different therapies and prognosis. However, the histological grading criteria remains elusive, and novel biomarkers may be helpful to differentiate the grade of PPTIDs. Immunohistochemical staining for CD24, PRAME, POU4F2, and HOXD13, and their clinicopathologic analyses were performed in pineal parenchymal tumors and other tumors in the pineal region. CD24 and PRAME were expressed in 9/11 (81.8%) and 8/11(72.7%) cases of PPTIDs grade III, compared with 6/18 (33.3%) and 5/18(27.8%) cases of PPTIDs grade II. The levels of CD24 and PRAME were significantly higher in PPTIDs grade III than grade II. However, there were no differences of HOXD13 and POU4F2 expression levels in PPTIDs grade II and grade III. Interestingly, high expression of CD24 and PRAME were prevalently found in high-grade tumors of the central nervous system. In addition, PPTIDs patients with high expression levels of CD24 and PRAME exhibited a significant shorter survival time. The results of PPTIDs grading by CD24 and PRAME were mostly consistent with WHO criteria, except for two cases. According to the prognostic information of patients, we found that the combination of CD24 and PRAME expression for grading PPTIDs might be more valuable than WHO criteria only. CD24 and PRAME are novel markers for grading and prognostic evaluation of PPTIDs that may be helpful to determine the therapeutic decision for PPTIDs patients. Abstract : Supplemental Digital Content is available in the text.